-12+7n=-5n-8(3n+6)

Simple and best practice solution for -12+7n=-5n-8(3n+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12+7n=-5n-8(3n+6) equation:



-12+7n=-5n-8(3n+6)
We move all terms to the left:
-12+7n-(-5n-8(3n+6))=0
We calculate terms in parentheses: -(-5n-8(3n+6)), so:
-5n-8(3n+6)
We multiply parentheses
-5n-24n-48
We add all the numbers together, and all the variables
-29n-48
Back to the equation:
-(-29n-48)
We get rid of parentheses
7n+29n+48-12=0
We add all the numbers together, and all the variables
36n+36=0
We move all terms containing n to the left, all other terms to the right
36n=-36
n=-36/36
n=-1

See similar equations:

| 20=4y-2+5+1/2 | | 6h-h+4=2 | | 2.04=t+t^2 | | 3(3x)+18=3x-5(3x-1) | | −4x+7=15;− | | 1-8t=7t+7 | | 8x-9=6x=21 | | 20=4y-2 | | 7(3k-5)=-7k+21 | | 3^81=x | | 6x+8=12+1+5x-3 | | (6+b)=5 | | –2h+–17=–3 | | -15.3=-7.5k=+55.2 | | 6x=2+5x | | |6+b|=5 | | x+1=-(5-x) | | m/8-65=-58 | | 38+7a=-3(-5a+1)+1 | | -2=-6+w | | 8/m-65=-58 | | -13-10m=-10-10m-3 | | 5(r−7)=80 | | x^2-5x-10=10 | | 12x+6=-12x+4 | | 2x+12=2(x+60 | | -31-3x=-2(8x-4) | | x+87+80=180 | | v+1/2=-3/5 | | 8h-9=6 | | -15-11p=11p-6 | | 8.50+2.50x=6+3x |

Equations solver categories